Savages [videorecording (DVD)] - Jenkins, Tamara, 1962-; Linney, Laura; Hoffman, Philip Seymour, 1967-2014; Bosco, Philip (20th Century Fox Home Entertainment, 2008)
Jon and Wendy Savage are two siblings who have spent their adult years trying to recover from their abusive father, Lenny. Suddenly, a call comes in that Lenny's girlfriend has died and he cannot care for himself. Lenny suffers from dementia and her family dumps Lenny on his children. Despite the fact Jon and Wendy have not spoken to Lenny for twenty years and he is even more loathsome than ever, the Savage siblings feel obliged to take care of him. Now together, brother and sister must come to terms with the new and painful responsibilities with their father. The siblings are forced to face the struggle with their now personal demons.